ASSOCIATION BETWEEN THE TYPE OF HOSPITAL WARD AND LENGTH OF STAY (LOS) OF INPATIENTS WITH HEART FAILURE - Tira Alfiani Laariya; MH. Muflihatul Ulfa; Fauzan Achmad Maliki (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Hospitals in Indonesia implemented several types of wards, from class III, class II, class I, and VIP. An indicator for assessing efficiency and quality of care is length of stay (LOS). Heart failure has become a worldwide issue with a high burden of medical costs. Objective: This study aimed to calculate the average LOS of heart failure patients and to identify their associations with the type of hospital ward. Methods: This cross-sectional study extracted data from the hospital information system to gather information on heart failure patients from 2021 to 2024 at PKU Muhammadiyah Yogyakarta Hospital, using purposive sampling. The data was analyzed using the Mann-Whitney U test. Results: The average LOS of all heart failure patients was 4,9 days (±2,9) with a median of 4,0 days (±3,0). Based on the type of wards, average and median LOS in class III were 5 days and 4 days; in class II were 4,2 days and 4 days; in class I were 5,9 days and 4,5 days; and VIP was 3,6 days and 3 days. There were no differences in LOS between class III and non-class III in heart failure patients with a p-value of 0,171. Conclusion: The average LOS of heart failure patients was 4,9 days with no differences between them and the type of ward.